PENERAPAN TRAINER INTERFACING MIKROKONTROLER DAN INTERNET OF THINGS BERBASIS ESP32 PADA MATA KULIAH INTERFACING - Hendra Kusumah; Restu Adi Pradana (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2019)
The absence of props remains a constraint on the learning process interfacing subjects where students have difficulty understanding the material obtained, besides because of the lack of microcontroller practice experience, students don't understand how to operate the microcontroller and also because of the lack of basic knowledge about the microcontroller. The design of the microcontroller interface trainer is intended as a teaching aid to help understand microcontroller interfacing using the UART, SPI, and I2C protocols and can be used as an Internet of Things teaching aid to help students practice monitoring and controlling input output on microcontrollers using smartphones over the internet. In designing this trainer, the author had made direct observations on learning activities in interfacing subjects and conducted questions and answers with several students. This trainer uses RFID, RTC and LCD modules as interfacing props that are connected to the ESP32 microcontroller, and there are components in the form of LEDs and potentiometers to practice the concept of the Internet of Things. The GPIO header pins and microcontroller interface pins expansion are also available on this trainer which can be connected with more modules and other components. Modules and components in the design of this trainer are connected with the ESP32 microcontroller in one integrated circuit board so as to provide practicality in its use.